Chapter 22: The African Union as a human security arrangement - M. Makinda, Samuel (Edward Elgar Publishing, 2022)
The African Union has articulated an approach to human security that incorporates political, social, economic, and environmental factors. However, Africa continues to experience wars, violent conflicts, and other threats to human security largely because the AU's mechanisms for dealing with these issues are inadequate. The AU's Peace and Security Council is poorly run, the relationships between the AU and Regional Economic Communities are not smooth, and Africa's capabilities to address human security threats are deficient. Despite the rhetoric about self-pacification, the AU human security architecture is dependent on outside funding, which enables outsiders to shape Africa's agenda. Moreover, the AU's activities under the African Peace and Security Architecture (APSA) have been state-centric and fallen short of addressing threats to human security. The AU needs to fully operationalize APSA and the African Governance Architecture, subscribe to their guiding principles and persuade its members to support the activities identified in their roadmaps.